New Keynesian Phillips Curve Estimation: The Case of Hungary /1981-2006/ - Aleksandar Vasilev (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper investigates for the presence of a New Keynesian Phillips (NKPC) curve in Hungary in the period 1981:3-2006:2, following the methodology proposed by Gali and Gertler (1999). They claim that a potential source of inflation may be the sluggish adjustment of real marginal costs to movements in output. The empirical model we test features forward-looking firms who pre-set prices for a couple of periods ahead, using Calvo (1983) pricing rule. In addition, measures of real marginal cost are used instead of the old-fashioned output gap. The reason is that marginal costs are a better proxy for the impact of the productivity gains on inflation, which the ad hoc measure output gap misses. We also estimate a hybrid version of NKPC, where some of the firms are backward-looking, and others are forward-looking in their price-setting behavior. Real marginal costs and forward-looking behavior are statistically significant and quantitatively important in the NKPC. However, there are some econometric issues to be considered, such as the weak identification of the parameters of the structural NKPC as well as those of the hybrid NKPC.
Keywords: C22; C26; E24; 330; New Keynesian Phillips curve; Hungary; instrumental non-linear GMM Estimation; weak identification